Serología en hepatitis virales (2011)
ABSTRACT: Infections due to hepatitis viruses A (HAV), B (HBV), C (HCV), D (HDV), and E (HEV) result in similar clinical and biochemical manifestations. Consequently, in order to identify with certainty the etiologic agents of hepatitis, it is necessary to carry out laboratory tests different from those used to assess liver function. Two kinds of tests are available for that purpose, namely: serological and molecular. The former are useful to detect viral antigens and the corresponding antibodies. The latter allow the detection of viral genomes. In order to diagnose current infections with any such viruses, except HCV, serological tests are sufficient. For HCV it is necessary to detect the viral genome. Molecular tests are very useful for follow-up purposes, and to fundament therapeutic decisions in patients with either HBC or HCV chronic infections. This article presents a review of the tests available to diagnose the different agents of viral hepatitis.